Novel genotyping approaches to easily detect genomic admixture between the major Afrotropical malaria vector species, Anopheles coluzzii and An. gambiae. (1st April 2021) - Caputo, Beniamino; Pichler, Verena; Bottà, Giordano; De Marco, Carlo; Hubbart, Christina; Perugini, Eleonora; Pinto, Joao; Rockett, Kirk A.; Miles, Alistair; della Torre, Alessandra
Abstract: The two most efficient and most recently radiated Afrotropical vectors of human malaria – Anopheles coluzzii and An. gambiae – are identified by single‐locus diagnostic PCR assays based on species‐specific markers in a 4 Mb region on chromosome‐X centromere. Inherently, these diagnostic assays cannot detect interspecific autosomal admixture shown to be extensive at the westernmost and easternmost extremes of the species range. The main aim of this study was to develop novel, easy‐to‐implement tools for genotyping An. coluzzii and An. gambiae ‐specific ancestral informative markers (AIMs) identified from the Anopheles gambiae 1000 genomes (Ag1000G) project. First, we took advantage of this large set of data in order to develop a multilocus approach to genotype 26 AIMs on all chromosome arms valid across the species range. Second, we tested the multilocus assay on samples from Guinea Bissau, The Gambia and Senegal, three countries spanning the westernmost hybridization zone, where conventional species diagnostic is problematic due to the putative presence of a novel "hybrid form". The multilocus assay was able to capture patterns of admixture reflecting those revealed by the whole set of AIMs and provided new original data on interspecific admixture in the region. Third, we developed an easy‐to‐use, cost‐effective PCR approach for genotyping two AIMs on chromosome‐3 among those included in the multilocus approach, opening the possibility for advanced identification of species and of admixed specimens during routine large scale entomological surveys, particularly, but not exclusively, at the extremes of the range, where WGS data highlighted unexpected autosomal admixture.